Localization of Macular Edema Region from Color Retinal Images for Detection of Diabetic Retinopathy - Budak, Umit; Sengur, Abdulkadir; Akbulut, Yaman (Ieee, 2017)
Exudates are among the first signs of diabetic retinopathy and one of the main causes of vision loss in diabetic patients. In this study, an approach based on clustering and morphological image processing has been proposed for detection of retinal exudates. Contrast-limited adaptive histogram equalization technique is used to make the location of the exudate areas more specific. In addition, the k-means clustering algorithm determines the locations of candidate regions. According to experimental results, it was observed that a majority of the pixels of the exudate regions were detected.
2017 International Artificial Intelligence and Data Processing Symposium (IDAP) -- SEP 16-17, 2017 -- Malatya, TURKEY
Keywords: Diabetic retinopathy; Exudate detection; K-means clustering